What causal relationship between financial stability and CSR? - (:unkn) unknown (My University, 2021)
The main objective of this paper is to compare the CSR behavior of European and African firms. In particular, it examines whether the CSR behavior of firms is linked to their financial stability. We tested this relationship using a panel vector autoregressive (PVAR) method. The study is based on a sample of 127 African companies and 519 European firms for the period 2010-2019. The results show that there is a unidirectional relationship between stability and CSR. For European firms, there is a positive and significant impact of CSR on stability. For African firms, stability contributes to the implementation of a sustainable development approach. In addition, our results reveal that there is a virtuous circle between governance dimension and the stability of European and African firms.
Keywords: African Research